New analytical approaches for verifying the origin of food - Brereton, P. (Paul) (Woodhead Publishing in food science, technology, and nutrition, 2013)
This book reviews new analytical methods on the food or beverage product's geographical origin, species, variety, and method of production together with applications to key commodities. Topics covered include labelling legislation and standards; new approaches for verifying the geographical origin of food using geospatial models and verifying species and varietal components of the food we eat; and new analytical methods to verify the origin of fish, honey and wine.